2022
DOI: 10.3390/ijms232113135
|View full text |Cite
|
Sign up to set email alerts
|

4-Thiazolidinone-Bearing Hybrid Molecules in Anticancer Drug Design

Abstract: Oncological diseases have currently reached an epidemic scale, especially in industrialized countries. Such a situation has prompted complex studies in medicinal chemistry focused on the research and development of novel effective anticancer drugs. In this review, the data concerning new 4-thiazolidinone-bearing hybrid molecules with potential anticancer activity reported during the period from the years 2017–2022 are summarized. The main emphasis is on the application of molecular hybridization methodologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…All compounds have been assessed for their ADMET profile in ADMET Predictor version 10.4 provided by the Simulation Plus software package [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All compounds have been assessed for their ADMET profile in ADMET Predictor version 10.4 provided by the Simulation Plus software package [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ...…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic heterocycles have been used as structural scaffolds to obtain a variety of bioactive compounds possessing antibacterial, antifungal, antiviral, and anti-parasitic activities [ 4 ]. Over the past decades, thiazolidine-2,4-diones (glitazones) have emerged as the most successful member of the 4-thiazolidinone compounds [ 5 ]. There are several drugs from this class of heterocycles, such as Lobeglitazone, Pioglitazone, Rosiglitazone, and Epalrestat, used broadly as oral anti-hyperglycemic agents for diabetes mellitus type 2 therapies, and recently, Ponesimod was approved for healing multiple sclerosis and psoriasis ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, docking studies also confirmed that 19 a showed the binding energy −21.8412 kcal/mol and two hydrogen bonds were created, one between the N of the quinazolidinone moiety and Lys721 and the other between the C=O of the thiazolidinone moiety and Met769. Additionally, the compound‘s planar aromatic rings created a Van der Waals connection with the amino acids Leu694, Val702, Phe699, Leu820, and Lys721 [83] …”
Section: Recent Development Of Different Nitrogen Containing Derivati...mentioning
confidence: 99%
“…Additionally, the compound's planar aromatic rings created a Van der Waals connection with the amino acids Leu694, Val702, Phe699, Leu820, and Lys721. [83] Thiazolyl-hydrazone analogues were developed and reported by Farghaly and colleagues as potential EGFR inhibitors. Compounds 20 a and 20 b (Figure 27) showed the best results in the MTT assay with IC 50 values of 1.24 μM (MCF7 cell line) and 3.61 M (HepG2 cell line), respectively.…”
Section: Chemistryselectmentioning
confidence: 99%
“…4-thiazolidinone-bearing hybrid molecules possess anticancer activity via various mechanisms of action, such as apoptosis induction, cell cycle arrest, and reactive oxygen species (ROS) induction. This group of compounds includes representants that act as kinase, tubulin, and carbonic anhydrase inhibitors [ 17 ]. Recently, we presented the multi-targeting mode of action of 2-{5-[(Z,2Z)-2-chloro-3-(4-nitrophenyl)-2-propenylidene]-4-oxo-2-thioxothiazolidin-3-yl}-3-methylbutanoic acid (Les-3331).…”
Section: Introductionmentioning
confidence: 99%